Mechanical force-assisted modulation of TiO2 nanowire-entangled hierarchical microstructures for photocatalysis application. (19th May 2022) - Zhang, Zeju; Chen, Lili; Zhao, Yanhui; Huang, Jielei; Ding, Chenfeng; Liu, Chunlei; Liu, Yaochun; Hong, Xiaofen; Liu, Yuan; Liu, Chunzhao
Abstract : A stirring-assisted solution-based approach was developed to construct new 3D TiO2 hierarchical structures with excellent photocatalytic performance for the degradation of organic pollutants. Abstract : Three-dimensional (3D) TiO2 hierarchical micromaterials assembled using high-aspect-ratio nano building blocks have exhibited many unique features of good structural stability, efficient mass transport/charge transfer properties and excellent light harvesting capability, which enable them to be successfully used for photocatalysis application. However, synthesis and structural control of the nano-/micro-materials pose serious challenges in materials design, such as requiring complex and time-consuming procedures, and harsh reaction conditions. Herein, we develop a simple wet-chemistry method combined with stirring procedure to construct new nanowire-assembled TiO2 submicron fibers with hierarchical structures. Results suggest that the mechanical force-driven stirring process increases the diffusion and surface reaction rate of intermediate hydrated titanate nanocrystal growth in the solution phase, leading to the generation of long tortuous nanowires and thereafter the formation of a new 3D nanowire-assembled hierarchical structure. The final 3D TiO2 nanowire-assembled micromaterials have a relatively large surface area of 184 m −2 g −1 with abundant hierarchical pores, which create an ideal micro-reactor for promoting the degradation of 2, 4-dichlorophenol and Rhodamine B under UV light. The good photocatalytic performance is attributed to the unique structure of the TiO2 hierarchical nano-micromaterials, including a hierarchical pore structure and a dual-phase-induced rich interface. This work presents a facile and cost-effective approach that is potentially competitive for scaling-up the production of novel TiO2 nano-micromaterials with desired porous hierarchy for advanced application.